Research of ultrastructure of the rat’s normal blood capillaries of thymus and its changes under influence of methyl tret-butyl ether - Kerechanin, Iryna (ScienceRise: Medical Science, 2017)
Aim of research is the study of the influence of benzene component, namely methyl tret-butyl ether on the structure of hemomicrocirculatory bed of a thymus. It is known that a thymus is a central organ of the immune system that plays an important role in the formation of the immune response to endo- and exogenous antigens. In the connection of growing environmental pollution, the number of diseases, connected with immune system pathologies essentially increased. Experts think that the increase of the number of immune diseases is a result of soil contamination as an inalienable factor of life activity. Methods of research: terms and conditions of water contamination with methyl tren-butyl ether, approximated to real ones were created for the study. The minimum for contamination is 1/1000 – 1/2000 of the mean toxic dose. Hemomicrocirculatory bed of rat’s thymus and its cells were studied under the influence of different doses (500 mg/kg; 50 mg/kg; 5 mg/kg; 0,5 mg/kg) of methyl tret-butyl ether. White laboratory rats were selected for the study because of well developed thymus and its morphological similarity to a human one. Results: general changes of hemomicrocirculatory vessels are reactive and adaptive ones (І and ІІ stages of pathological process), dystrophic and alterative (ІІІ stage), changes of endotheliocytes and basal membrane in all links of hemomicrocirculatory bed. The manifestation of reactive changes is the change of endotheliocytes configuration, microclasmatos and vesiculation. The adaptation of reactive changes is directed on stabilization of the endotheliocyte order. It is manifested as vesiculation transformation from the transport to membranoplastic type. Conclusions: Morphological study of the vascular ultrastructure of hemomicrocirculatiry bed using electric transmissive microscopy proves that at methyl tret-butyl ether penetration in rat’s organism, its effect results in ultrastructural changes of the microhemocirculatory bed and has a cumulative character